Gerak Tubuh Untuk Perkembangan Motorik Kasar Anak Usia 5-6 Tahun Di Raudhatul Athfal Al-Hikmah - Mahmudah, Titik; Muflihah Baktiar; Irmawati (Celebes Journal of Elementary Education, 2024)
This research aims: (1) To describe and implement stimulation of gross motor physical development, (2) To describe and carry out various kinds of body movements that can stimulate aspects of gross motor physical development, (3) Apply methods that are beneficial for physical motor development rude to children aged 5-6 years. The qualitative descriptive approach method was used by researchers to obtain data through observation, question and answer, and documentation. From the results of this research, it was found that the role of body movement is very beneficial for the physical development of gross motor skills, namely through various kinds of games designed by teachers using methods that can encourage motor activities to be developed. The methods used can include jumping activities with two children with one right foot or left foot or two feet together, running, moving a ball, games using hula-hoops and other games that require power from large muscles. Support and cooperation between teachers and parents is needed in providing stimulation for gross motor development in children aged 5-6 years. Thus, understanding the Child Development Achievement Level Standards (STPPA) can be the basis for developing a holistic learning approach focused on the gross motor development of early childhood. Because it can help to ensure that children receive stimulation appropriate to their developmental stage.